Analisis Pengaruh Penilaian Kinerja dan Gaya Kepemimpinan Transformasional terhadap Kinerja Karyawan - Ade Ramli; Sinollah (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2025)
The aim of this research is to determine and analyze the influence of performance appraisal and transformational leadership style on employee performance. This research design uses a quantitative approach with data collection methods using questionnaires on Malang Regency Transportation Service employees with a sample of 50 employees. The analytical method in this research uses multiple linear regression analysis. The results in this study show the influence of: (1) Performance appraisal directly has a significant effect on employee performance. (2)The transformational leadership style directly has a significant effect on employee performance. (3) Performance appraisal and transformational leadership style directly have a significant effect on employee performance. For this reason, if a leader wants to improve employee performance by paying attention to performance appraisals and leadership styles towards employees